German Medical Informatics Initiative: Unlocking Data for Research and Health Care - Gehring, Stefanie; Eulenfeld, René (Methods of Information in Medicine, 2018)
This article is part of the Focus Theme of Methods of Information in Medicine on the German Medical Informatics Initiative. The Medical Informatics Initiative of the German Federal Ministry of Education and Research will make use of the potential of digitalization in the field of medicine in Germany. The aim is to improve the possibilities for medical research and patient care through innovative IT solutions. In an initial step, data integration centres will be set up at university hospitals to ensure the technical and organizational conditions necessary for multi-site exchange of data between health care and clinical and biomedical research. The Federal Ministry of Education and Research will provide a total of around EUR 150 million for this initiative over the next four years.